Pelatihan Membatik Pewarna Alami dan Pengenalan Teknologi Mordanting Kitosan pada Balai Agung Cendana Semaki, Yogyakarta - Evitasari, Rachma Tia; Mufrodi, Zahrul; Robi’in, Bambang (Universitas Nusantara PGRI Kediri, 2023)
The strategic plan for the development of the Semaki area is to develop regional-based economic, social and cultural communities with various training programs. One of which is handmade batik craftsmen who is in UKM Balai Agung Cendana Batik Tulis. The problems are high production costs and the length of production time in making batik. The purpose is to increase the knowledge and capacity of partners in producing batik with natural dyes by introducing natural dyeing technology so as to reduce the stages of the process so as to reduce production costs. Methods and approaches in implementing this activity are counseling and training. Community service activities at Balai Agung Cendana Batik Tulis were able to increase participants' knowledge in drawing motifs, wax painting, dyeing processes, and pre-mordanting with chitosan up to 100%. The batik training provided to the community was also able to improve the community's skills in drawing and painting batik up to 92% and the skills of dyeing fabrics with natural dyes and chitosan mordanting up to 98%.